JUSTIFICATION OF THE NEED FOR A UNIFIED APPROACH TO THE MANAGEMENT OF THE PUBLIC EXTERNAL DEBT OF THE PARTICIPATING COUNTRIES OF THE EURASIAN ECONOMIC UNION - O. Revzon; R. Knyazev; Y. Gushchin (Вестник университета)
In article it is told about the Eurasian Economic Union, stages of his formation and features of his budget, the question of the main macroeconomic indicators of the countries-participants of the Union, and also a question of dynamics and structure of their public debt.